DEVELOPMENT OF CROSSWORD PUZZLE MEDIA TO IMPROVE INDONESIAN LITERACY SKILLS OF GRADE II STUDENTS - Dewi Chairunnisa Siregar; Faridah (SOSIOEDUKASI, 2026)
This study aims to develop a crossword puzzle learning medium that is feasible, practical, and effective in improving the Indonesian language literacy skills of second-grade students in the topic of recognizing experiences. The method used was Research and Development (R&D) with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The study subjects were 20 second-grade B students at MIN 9 Medan City. Data collection techniques included observation, documentation, questionnaires, expert validation, and pretests and posttests. Data analysis was conducted using a Likert scale, feasibility percentage, and the N-Gain test to measure learning outcomes. The results showed that the developed crossword puzzle media achieved an average validation score of 84.58%, categorized as very valid and very practical. The validation results included the media aspect (93.75%), and the material and language aspects (80% each). The trial results showed an increase in students' literacy skills, indicated by an increase in the average score from 66.21 in the pretest to 86.36 in the posttest. Furthermore, the N-Gain analysis result of 0.59 is within the moderate criteria, indicating a significant improvement. Student and teacher responses to the use of the media also showed very positive results, with increased levels of activity and interest in learning. In conclusion, the crossword puzzle media developed has proven to be feasible, practical, and quite effective in improving the Indonesian language literacy skills of second-grade students and can be used as an alternative, innovative and enjoyable learning medium.